Genetic and Environmental Aspect of Preweaning Weight Gain of Pigs in South Western Nigeria - Leigh, A. O. (Faculty of Agriculture, University of Ife, 2015)
Data recorded at Fasola Stock Farm for 451 litters and involving 66 boars and 4 breeds of pigs were analysed to investigate the environmental and genetic factors causing variation in preweaning weight gains of pigs. Two specific traits - average pig weight gain from birth to weaning (PPWG), and litter weight gain from birth to weaning (LPWG) were studied. The two traits did not show significant effects of breed, parity of dam, season or interaction (P>. 05). Only PPWG showed highly significant effects of year (P < .05). However, litter size at birth and at eight weeks, and average pig weight at birth had significant influence on both traits. Estimates of heritability based on paternal half-sib correlation were 0.19 to 0.15 and 0.49 to 0.20 for PPWG and LPWG respectively. Both the phenotypic and genetic correlations between the two traits were high and positive (rP = .75 and rG = .98). It is suggested that weight gain from birth to weaning at 8 weeks instead of weaning weight per se should be used as criterion for making initial selections of future breeders.